Motivasi Kerja Karyawan Pada Ritel Modern Era Revolusi Industri 4.0 dikaitkan dengan Prestasi Kerja. - Albert Kurniawan Purnomo (MBIA, 2019)
The competition between modern physical retailers in the industrial revolution 4.0 have an impact on the number of physical retail stores that have been forced to close, due to declining turnover. This encourages management to focus more on the performance of employees to be able to achieve. Outstanding employees are able to exceed the target set by the company. The factors that are thought to affect work performance are motivation, knowledge, ability, expertise, education, experience, training, interests, and attitudes. In this study, the factors that are focused are motivational factors. The theory that became the basis was pioneered by McClelland, which included achievement motivation, power motivation, and affiliate motivation. This research method is a quantitative method, with an expalanatory causal approach. Data collection techniques by distributing questionnaires to 31 retail employees from 3 branches. Data analysis using WarpPLS 6.0 software. The results of the study explain that overall motivation affects work productivity.